Труд и зарплата на предприятиях машиностроения в условиях самофинансирования - Жуков Л. И. Леонид Иванович; Горшков В. В. Владимир Валентинович; Ловков В. А. Владимир Анатольевич; Неверовский Л. В. Лев Викторович; Жуков Л. И. (Машиностроение)
Исключено из фонда НТБ ТПУ